Emigrant Voyages from the UK to North America and Australasia, 1853-1913 - Timothy J. Hatton (Institute of Labor Economics (IZA), 2023)
Studies of the determinants of emigration from Europe from 1850 to 1913 include the gains to migrants but often neglect the costs. One component of those costs is earnings forgone on the voyage. In this paper I present new data on the voyage times for emigrants from the UK traveling to the United States and to Australia. Between 1853-7 and 1909-13 the voyage time from Liverpool to New York fell from 38 days to just 8 days (or 79%). Over the same years, the emigrant voyage to Sydney fell by more in absolute terms, from 105 days to 46, but by less in relative terms (56%). Differences in profiles of travel times are explained with a focus on the relative efficiency of sail and steam and (for Australia) the use of the Suez Canal. Data series for fare prices and foregone wage costs are combined to create new series on the 'total' cost of emigrant voyages. Econometric analysis of UK emigration to the US, Canada and Australia supports the view that time costs mattered.
Keywords: F22; O33; N73; 330; international migration; steam ships; voyage times